Mental health care utilisation and access among refugees and asylum seekers in Europe: A systematic review - Satinsky, Emily; Fuhr, Daniela C.; Woodward, Aniek; Sondorp, Egbert; Roberts, Bayard (Health policy (Amsterdam), 2019)
•Refugees and asylum seekers in Europe experience high mental health needs.•This population exhibits low contact coverage of specialist MHPSS services.•This population presents more frequently with physical health complaints.•Barriers to access include: language, stigma, low awareness, and variant help-seeking behaviours. Refugees and asylum seekers often have increased mental health needs, yet may face barriers in accessing mental health and psychosocial support (MHPSS) services in destination countries. The aim of this systematic review is to examine evidence on MHPSS service utilisation and access among refugees and asylum seekers in European Union Single Market countries. Four peer-reviewed and eight grey literature databases were searched for quantitative and qualitative literature from 2007 to 2017. Access was categorised according to Penchansky and Thomas’ framework and descriptive analyses were conducted. Quality of studies was assessed by the Newcastle-Ottawa scale and the Critical Appraisal Skills Programme checklist. Twenty-seven articles were included. The findings suggest inadequate MHPSS utilisation. Major barriers to accessing care included language, help-seeking behaviours, lack of awareness, stigma, and negative attitudes towards and by providers. Refugees and asylum seekers have high mental health needs but under-utilise services in European host countries. This underutilisation may be explained by cultural-specific barriers which need to be tackled to increase treatment demand. Training health providers on cultural models of mental illness may facilitate appropriate identification, referral, and care. Based on these findings, it is crucial to review policies regarding MHPSS provision across the EU.